THE INFLUENCE OF THE OPEN-ENDED LEARNING MODEL ON CREATIVE THINKING ABILITY IN TERMS OF ADVERSITY QUOTIENT - Darwanto Darwanto; Intan Nurmala (Universitas Muhammadiyah Lampung, 2025)
Creative thinking ability is one of the essential skills that students must possess and is also a mandatory competence in accordance with educational objectives. The low level of creative thinking ability among Grade X students at MAN 2 Lampung Utara is one of the main concerns of this study. The aim of this research is to determine how students' creative thinking ability is influenced by the open-ended learning paradigm and Adversity Quotient (AQ), and to examine how the interaction between the learning model and AQ affects creative thinking ability. All Grade X students at MAN 2 Lampung Utara were involved as research subjects, with Class X-4 serving as the control group and Class X-5 as the experimental group, selected through cluster random sampling. An essay test consisting of four questions, validated both by experts and empirically, was used to measure creative thinking ability. The Adversity Response Profile (ARP) instrument, consisting of 30 items, was used to assess AQ. Two-way ANOVA was employed to evaluate the data. The conclusions drawn from the analysis are as follows: (1) students' creative thinking ability is significantly influenced by the use of the open-ended learning model; (2) students' creative thinking ability is significantly influenced by AQ; and (3) no interaction was found between the variables.